2018
DOI: 10.1093/nar/gky1217
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that a catalytic glutamate and an ‘Arginine Toggle’ act in concert to mediate ATP hydrolysis and mechanochemical coupling in a viral DNA packaging motor

Abstract: ASCE ATPases include ring-translocases such as cellular helicases and viral DNA packaging motors (terminases). These motors have conserved Walker A and B motifs that bind Mg2+-ATP and a catalytic carboxylate that activates water for hydrolysis. Here we demonstrate that Glu179 serves as the catalytic carboxylate in bacteriophage λ terminase and probe its mechanistic role. All changes of Glu179 are lethal: non-conservative changes abrogate ATP hydrolysis and DNA translocation, while the conservative E179D change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 72 publications
2
19
1
Order By: Relevance
“…This rotation could either actively pull the trans-acting loops of the nieghboring subunit with it, or passively move these loops by relieving the tension imposed by the lid subdomain in the ATP-bound configuration. This agrees well with prior structual, biochemical, and simulation data that suggest both ATP binding and nucleotide release actuate rotation of the lid subdomain (Hilbert et al, 2015;Ortiz et al, 2019).…”
Section: Nucleotide Exchangesupporting
confidence: 89%
See 2 more Smart Citations
“…This rotation could either actively pull the trans-acting loops of the nieghboring subunit with it, or passively move these loops by relieving the tension imposed by the lid subdomain in the ATP-bound configuration. This agrees well with prior structual, biochemical, and simulation data that suggest both ATP binding and nucleotide release actuate rotation of the lid subdomain (Hilbert et al, 2015;Ortiz et al, 2019).…”
Section: Nucleotide Exchangesupporting
confidence: 89%
“…These differences may be due to subtle differences in the way ATP is bound; subunits wherein adenosine binds the Q-motif have lid subdomain motion projected towards the ATPase binding site, whereas subunits wherein adenosine is not bound to the Q-motif do not. Although prior predictions suggested that the apoto-ATP-bound transition is characterized by an "open-to-closed" transition (Ortiz et al, 2019), our simulations suggest this transition could also be characterized as a "flexible-to-rigid" state transition.…”
Section: Flexibility and Variability Of Subunitscontrasting
confidence: 75%
See 1 more Smart Citation
“…We note that the Walker A arginine residue moves into the binding pocket upon ATP-binding and moves out of the binding pocket in the absence of the γ-phosphate. We have previously reported that this conserved Walker A arginine in phage λ functions analogously to the “sensor II motif” arginine found in AAA+ enzymes, whose role is to sense the presence of the γ-phosphate and induce further conformational changes (10). The results presented here further support this assignment.…”
Section: Resultsmentioning
confidence: 99%
“…A common feature among ASCE enzymes is the presence of a P-loop/Walker A (WA) and Walker B (WB) motifs which bind ATP and catalyze hydrolysis, respectively (8, 9). The feature that distinguishes ASCE enzymes from other superfamilies of ATPases is the presence of a conserved glutamate residue downstream of the WB motif that is necessary for catalytic activity (6, 10, 11). Like most ASCE systems, viral packaging ATPases assemble as oligomeric rings that thread their biopolymer substrate through their central pores (12, 13).…”
Section: Introductionmentioning
confidence: 99%